Pengaruh Promosi Jabatan Dan Kompetensi Terhadap Kinerja Karyawan - Linda Mulia Permatabunda; Heru Setiawan (Jurnal Riset Mahasiswa, 2023)
This study aims to empirically examine the Effect of Position Promotion and Competence on Employee Performance Case Study at PT Bank Tabungan Negara KCU Bandung both simultaneously and partially. This study uses a research method that is descriptive and verification with a sample of 70 respondents. Data collection techniques used were observation, interviews and distributing questionnaires. The data analysis method used is multiple linear regression analysis, multiple correlation analysis, coefficient of determination analysis and hypothesis testing. The results showed that the Promotion of Position, Competence and Employee Performance of PT Bank Tabungan KCU Bandung State can be said to be good, but there are still some that are not good. Position and Competence Promotion has an influence on employee performance, which is 79.1%. The influence of the dominant independent variable is Competence with a coefficient of 71.8%, while the Job Promotion coefficient is 16.4%.